2009
DOI: 10.1016/j.molcel.2009.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Tumor Suppressor CYLD by the Breast Cancer Oncogene IKKɛ Promotes Cell Transformation

Abstract: Summary The non-canonical IKK family member IKKε is essential for regulating anti-viral signaling pathways and is a recently-discovered breast cancer oncoprotein. Although several IKKε targets have been described, direct IKKε substrates necessary for regulating cell transformation have not been identified. Here, we performed a screen for putative IKKε substrates using an unbiased proteomic and bioinformatic approach. Using a positional scanning peptide library assay we determined the optimal phosphorylation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
230
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(243 citation statements)
references
References 40 publications
8
230
1
4
Order By: Relevance
“…7D). Although phosphorylation of Cyld on serine has recently been reported (Hutti et al, 2009), this is the first report demonstrating Cyld tyrosine phosphorylation.…”
Section: Cyld Tyrosine Phosphorylation Is Essential For Dr Formationmentioning
confidence: 68%
“…7D). Although phosphorylation of Cyld on serine has recently been reported (Hutti et al, 2009), this is the first report demonstrating Cyld tyrosine phosphorylation.…”
Section: Cyld Tyrosine Phosphorylation Is Essential For Dr Formationmentioning
confidence: 68%
“…Très récemment, les travaux du groupe de L. C. Cantley ont permis de caractériser un motif optimal, X-X-X-Y/F/P/M-X-pS-L/I/M/F-X-Y/W/ F-X, de phosphorylation par IKKε. En utilisant ce motif par une technique bio-informatique, plusieurs substrats potentiels d'IKKε ont été identifiés [11]. En revanche, pour d'autres substrats d'IKK, comme IκBα ou le récepteur de l'oestrogène α (ERα + ), les sites contenus dans les séquences ciblées par la kinase ne correspondent pas à ce motif [4,12], suggérant que ce motif linéaire caractérisé in vitro ne reflète pas totalement la sélectivité d'IKKε qui semble être moins forte in vivo.…”
Section: Ikke Un Membre De La Famille Des Kinases Ikkunclassified
“…L'activation d'IRF-7 et de STAT1 n'a, à notre connaissance, pas été étudiée dans ce contexte. NF-κB joue un rôle dans diverses étapes REVUES Ser418 déclenche une augmentation de l'activité de NF-κB [11]. Il est particulièrement intéressant de noter que l'ablation de l'expression de CYLD provoque une activation constitutive d'IKKε dans les cellules dendritiques et dans des fibroblastes embryonnaires humains [30].…”
Section: Phosphorylation De Facteurs De Transcription D'une Voie Ikkeunclassified
“…In cancer, tumor cells death results in release of numerous proteic or nucleic DAMPs that activate TLRs of both immune/stromal cells and epithelial cancer cells. Increasing evidence has indicated that TLRs expression by cancer cells and immune cells seems to be twofold by either promoting or inhibiting tumor progression [6,15,16].…”
Section: Introductionmentioning
confidence: 99%